2011
DOI: 10.1177/1742766511427503
|View full text |Cite
|
Sign up to set email alerts
|

News framing of the ‘Detroit Bomber’ in the Nigerian press

Abstract: the world was greeted by the story of a young Nigerian who, according to the reports, attempted to destroy a US airliner to Detroit, Michigan. His name is Umar Farouk Abdulmutallab. This story was shocking not only to the outside world but also to Nigerians because of the background of the alleged perpetrator: he had received a sound education right from childhood, and had attended some of the best schools including University College London.A point of interest here is that Nigeria is a country that is regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…From research question three, the finding showed that majority of the respondents accede to have positive perception on how news stories on COVID-19 pandemic are framed. This finding is in tandem with result of an earlier study carried out by Yusha'u (2011), who held that framing, which describes the way the media see a thing or the way they want the audience to see a story, event of happening is achieved by making the news angles salient, based on selection of words, language among other features, often to protect editorial interests or ownership philosophy. This process according to him has significant relevance to the way people interpret and react to the entire story.…”
Section: Discussion Of Findingssupporting
confidence: 81%
See 1 more Smart Citation
“…From research question three, the finding showed that majority of the respondents accede to have positive perception on how news stories on COVID-19 pandemic are framed. This finding is in tandem with result of an earlier study carried out by Yusha'u (2011), who held that framing, which describes the way the media see a thing or the way they want the audience to see a story, event of happening is achieved by making the news angles salient, based on selection of words, language among other features, often to protect editorial interests or ownership philosophy. This process according to him has significant relevance to the way people interpret and react to the entire story.…”
Section: Discussion Of Findingssupporting
confidence: 81%
“…In journalism practice, framing means the way the media see a thing or the way they want the audience to see a story, event of happening. This, the mass media achieve by making the news angles salient, based on selection of words, language among other features, often to protect editorial interests or ownership philosophy (Yusha'u, 2011). This process also has significant relevance to the way people interpret and react to the entire story.…”
Section: Coronavirus Case In Nigeriamentioning
confidence: 99%
“…How media shape and present such health crises have been studied through agenda-setting and framing theories of the media. Framing refers to the exclusion or inclusion of categories, concepts and contexts in the news (Yusha’u 2011). Research points out that the media’s framing of a general issue affects people’s understanding of that issue (Shehata 2010).…”
Section: Introductionmentioning
confidence: 99%